Quality and fodder yield of forage black sorghum (Sorghum almum) for silage in mature ages. - Boschini-Figueroa, Carlos; Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2005)
The study was carried out to determine the chemical composition and production yield of dry matter and nutritional content per area in shoots 91 to 161 days old, and to explore the options for harvest silage. The study took place at the Alfredo Volio Mata Experimental Station of the University of Costa Rica. The first samples were taken at 91 days and were re-taken every 14 days until they were 161 days old. Biomass production was measured and the content of dry matter, crude protein, ashes, neutral detergent fiber increased as the maturity of the plants increased, to a rate of 0.19%/day in leaves and 0.26%/day in stems, for a 0.22%/day in the whole plant. The yield of green matter reached its maximum at 135 days, the leaves at 121 days, and the stems at 144 days. The maximum production of dry matter, crude protein and neutral detergent fiber per hectare was obtained from shoots of 130 to 135 days old. The best quality was found at 91 days, with 12% of dry matter and 14% crude protein. From that age on, the accumulation of dry matter increased at a rate of 62 kg/ha/day (a concentration of 2% every 10 days), of which 48 kg were of neutral detergent fiber and an average of 2 kg of lignin. The content of crude protein decreased 1% every 10 days.